Etiología y susceptibilidad antimicrobiana de la neumonía intrahospitalaria asociada a ventilación mecánica - Gómez Zare, Juan Francisco (2015)
To determine the etiology agent and his antimicrobial susceptibility of the ventilator associated pneumonia of the Department of Emergency and Critical Care of Hospital Belen de Trujillo during the period 2011-2013 Material and method: A retrospective descriptive study by review of medical records and antibiograms of the Intensive Care Unit (ICU) adult and the Cardiopulmonary Reanimation Unit (CPRU) patients that developed ventilator associated pneumonia, was identified the germs and their antimicrobial susceptibility patterns. Results and conclusions: 126 antibiograms corresponding to 70 patients were obtained. The etiologic agents most frequently isolated in the ICU were: Pseudomonas aeruginosa (45.9%), Staphylococcus aureus (11.4%) and Klebsiella pneumonia (10.3%). In the CPRU were: P. aeruginosa (48.7%), K. pneumoniae (15.3%) and S. aureus (5.1%). P. aeruginosa in the ICU showed high antimicrobial resistance (> 60%) in the CPRU the antimicrobial resistance was very high (≥70%). K. pneumonia in both ICU and CPRU showed very high resistance (≥70%). S. aureus in the ICU and the CPRU presented 100% resistance to oxacillin and 100% sensitivity to vancomycin and linezolid